Pembuatan Model Pemberdayaan Masyarakat Pesisir Sesuai Profesi Menggunakan Pendekatan Perpustakaan Berbasis Inklusi Sosial - Verry Mardiyanto (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research explains the development of a model for empowering coastal communities based on their professions using a socially inclusive library approach. The case study was conducted in Banten Lama, Kota Serang, Banten Province. The objective of this research is to find an appropriate model for empowering the community, tailored to the existing professions in coastal communities. The socially inclusive library approach is employed as a means to empower the community and improve their well-being. The research method used in this study is descriptive qualitative research, focusing on the functions and roles of libraries in increasing community engagement in terms of well-being. The findings of this research present a model for empowering coastal communities based on their respective professions. In the smallest context, the library is represented by a community reading park, which serves as an agent of change in the coastal community. The conclusion in this study is that the social inclusion-based library model is adapted to community professions adapted to the support of collaboration between regional libraries, village libraries and community reading library. In addition, this community empowerment model is described in three models according to the profession, namely the community empowerment model for the fisherman profession, the trade profession and the tour guide profession